A Flexible, User-friendly Front End for Bibliographic Retrieval: Making CAN/OLE Easier to Use - Westel, E.R.; Auster, E.W.; Lamb, M.R. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2022)
see PDF